[tex]1.39\ a)\\\\(-1\frac{3}{4} )*(-2,5)*3\frac{5}{6}*(-6)* \frac{4}{7}*2=(- \frac{\not{7}^1}{\not{4}^1} )*(-\frac{\not{25}^5}{\not{10}^2})* \frac{23}{\not{6}^1}*(-\not{6}^1)* \frac{\not{4}^1}{\not{7}^1}*2=\\\\=-\frac{5}{\not{2}^1 }*23*\not{2}^1 =-5*23=-115\\\\b)\\\\0,375*4* \not{\sqrt{6}}^1 *(- \frac{1}{\not{\sqrt{6}}^1} *(-0,25)*(-8)=1,5*(-1)* 2=-3\\\\c)\\\\ \frac{1}{21}* \frac{25}{7}*0,7* \frac{1}{3,5} *(-7)*(-\frac{42}{5})= \frac{1}{\not{21}^1}* \frac{\not{25}^5}{\not{7}^1}* \frac{\not{7}^1}{\not{10}^2}* \frac{1}{ \frac{35}{10}} *(-7)*(-\frac{\not{42}^2}{5})=\\\\= \frac{ \not{5}^1}{\not{2}^1}*\frac{10}{\not{35 }^5} *(-\not{7}^1)*(-\frac{\not{2}^1}{ \not{5}^1}) =\frac{10}{5} =2[/tex]
[tex]\\\\d)\\\\3,6*(- \frac{1}{2})*(-\frac{5}{6} )*4*0,25 = \frac{\not{36}^6}{\not{10}^2 }*(- \frac{1}{2})*(-\frac{\not{5}^1}{\not{6}^1} )*1 = \frac{6}{4}=\frac{3}{2}=1\frac{1}{2}[/tex]